2008
DOI: 10.1167/8.14.20
|View full text |Cite
|
Sign up to set email alerts
|

The significance of microsaccades for vision and oculomotor control

Abstract: Over the past decade several research groups have taken a renewed interest in the special role of a type of small eye movement, called ‘microsaccades’, in various visual processes, such as the activation of neurons in the central nervous system, or the prevention of image fading. As the study of microsaccades and their relation to visual processes goes back at least half a century, it seems appropriate to review the more recent reports in light of the history of research on maintained oculomotor fixation, in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
187
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(197 citation statements)
references
References 169 publications
10
187
0
Order By: Relevance
“…to 2.7 saccades/s for subject R.S. Whereas saccades were frequent, microsaccades-defined as saccades with amplitudes of Ͻ30 arcmin-were extremely rare, a result that is in line with previous reports of both head-free (Malinov et al, 2000) and head-fixed studies (Collewijn and Kowler, 2008;Kuang et al, 2012) Even in the absence of microsaccades, the eyes moved considerably during fixation because of ocular drift, the smooth motion always present in the intervals between saccades. In all subjects, ocular drift reached velocities of several degrees per second on both the horizontal and vertical axes, with averages Ͼ1°/s (Fig.…”
Section: Fixational Head and Eye Movementssupporting
confidence: 89%
See 2 more Smart Citations
“…to 2.7 saccades/s for subject R.S. Whereas saccades were frequent, microsaccades-defined as saccades with amplitudes of Ͻ30 arcmin-were extremely rare, a result that is in line with previous reports of both head-free (Malinov et al, 2000) and head-fixed studies (Collewijn and Kowler, 2008;Kuang et al, 2012) Even in the absence of microsaccades, the eyes moved considerably during fixation because of ocular drift, the smooth motion always present in the intervals between saccades. In all subjects, ocular drift reached velocities of several degrees per second on both the horizontal and vertical axes, with averages Ͼ1°/s (Fig.…”
Section: Fixational Head and Eye Movementssupporting
confidence: 89%
“…For example, the VOR gain varies with the distance of the fixation point (Paige, 1989;Schwarz and Miles, 1991;Crane and Demer, 1997;Paige et al, 1998;Wei and Angelaki, 2004). In addition, optical adaptation experiments found that subjects converge on their own idiosyncratic degree of compensation, even though, in doing this, they progressively modify the VOR gain so that the stimulus on the retina is stationary at some point during the course of adaptation (Collewijn et al, 1981). In keeping with these previous findings, our results strongly support the proposal that the function of ocular drift is the maintenance of a specific range of retinal image motion that facilitates the acquisition and processing of visual information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These microsaccades, also called fixational saccades, are rapid, jerky eye movements smaller than 15 minutes of arc, that follow the main sequence and, with a velocity <50º/s [15] . In the unrestrained head condition, as in our study, they are irrelevant but still occur [16] . Because of this, we decided to include some criteria to rule them out.…”
Section: Discussionsupporting
confidence: 61%
“…We proposed that either presaccadic suppression (Reppas et al 2002;Royal et al 2006) during the detection task or peri-microsaccadic enhancement (Collewijn and Kowler 2008;Martinez-Conde et al 2004, 2013 during the fixation task could explain this difference in sensitivity. In the current study, however, we did not observe any significant difference in LGN P ON or P OFF neural sensitivities between the two tasks.…”
Section: Comparison Between the Detection And The Fixation Tasksmentioning
confidence: 99%